SOFT SKILLS PADA PELAKSANAAN MAGANG DUNIA USAHA/DUNIA INDUSTRI - Purwaningsih, Ika Juni Sartika; Witurachmi, Sri; Zoraifi, Renata (Tata Arta : Jurnal Pendidikan Akuntansi, 2017)
ABSTRACTThe objectives of this research are to investigate: scores of discipline, initiative, and communication indicators in the implementation of business internship/industrial internship. This research used the de-scriptive quantitative research method. Its population was 65 students of the class of 2013, the Bachelorâs Degree Program in Education, Surakarta who had completed their internship program. They all also be-came the samples of this research, which were determined through census sampling technique. The results of the z test shows that the studentsâ scores of discipline, initiative, and communication are 79.61, 66.67, and 61.54 respectively.Keywords: Soft skills, Discipline, Initiative, Communication, and Business Internship or Industrial In-ternshipABSTRAKPenelitian ini bertujuan untuk mengetahui tinggi skor indikator disiplin, inisiatif, dan komunikasi mahasiswa pada pelaksanaan magang dunia usaha/dunia industri (du/di). Sejumlah 65 mahasiswa angkatan 2013 salah satu Prodi di Fakultas Kependidikan yang telah melaksanakan magang menjadi popu-lasi sekaligus sampel dalam penelitian ini. Penelitian ini merupakan penelitian deskriptif kuantitatif dan teknik pengambilan sampelnya adalah sensus sampling. Berdasarkan analisis data dengan menggunakan uji z dan skor 100, hasil penelitian menunjukkan bahwa tinggi skor indikator disiplin, inisiatif, dan komu-nikasi mahasiswa yaitu: (79,61), (66,67) dan (61,54).Kata kunci: Soft skills, Disiplin, Inisiatif, Komunikasi, Magang Dunia Usaha/Dunia Industri